Does a Unified Energy Equation Contain the Higgs Field? - Marcus O. Durham; Robert A. Durham (IEEE Access, 2013)
A comprehensive equation for natural and physical systems including electric and magnetic, mass, and wave interactions has long been an objective of engineers and scientists. Dynamic energy appears to be one possible technique. A method of mathematics is used with curved space vectors which greatly reduces the calculus. The vector relationship between cyclic time and reference time is identified. A diffusion relationship is developed which has the potential for describing the Higgs field. The diffusion is defined in terms of a volume gradient varying with reference time. By judicious definition of dynamic energy, the diffusion is also a direct relationship of electrical charge and magnetism with waves or photons, and mass.